Campos organizacionais em transformação: o caso do jazz americano e a música popular brasileira - Kirschbaum, Charles (2006)
The Neo-Institutional theory defines Organizational Fields as social spaces where actors share rules, interpretative schemata and consent with established institutions. From this perspective, one expects that field’s actors adopt and diffuse social forms. This conception of field has been expanded in order to include the phenomena of conflict and innovation. By exploring the Jazz and the MPB fields, this thesis approaches the transformations in fields of music production. First, it investigates the theoretical relationships between the concept of field and social networks, by exploring the convergence of Bourdieu’s and Harrison White’s theories. Although I don’t propose a synthesis between these two approaches, I advocate that they are complementary. Hence, I suggest that social changes might occur in tandem with the uncoupling between the social network structure and the concentration of opportunities. By reconstructing the social networks among Jazz musicians, from 1930 to 1969, I obtain a topography of band leaders and their respective styles. The findings suggest one might explain the locus of new style emergence by the field’s structure evolution. The internal changes in a field impacted several musicians’ careers. I built a “typical” career-path, which suggests a track to be covered in order to attain success. In contrast, the change in the field’s structure and meta-logics favored several musicians who didn’t follow the typical path. This contrast attempts to shed light on the individual action, which helped in turn to change the field’s logic. A field’s institutionalization allows the identification of those legitimate styles, in contrast with those that are segregated. Thus, a field’s permeability articulates its autonomous generation of norms with external elements. Again, this permeability reflects a field’s structure and logics change. By exploring the penetration of Bossa Nova in the Jazz field, I analyzed how Jazz critics participated in the legitimating and in the translating processes of Bossa Nova. This cross-influence occurred in tandem with a redefinition of both fields’ boundaries. The communication between two different fields turns to be a crucial explanative factor in the emergence of new fields. The communication between the MPB and the pop music groups (mostly Jovem Guarda) was accomplished by Tropicalists. The creation of a new position made possible the articulation of two social spaces that were polarized. It seems evident the role of conflict underlying these dynamics: the conflict within the jazz field allowed the opening and emergence of a plurality of styles that articulated in several ways the Jazz tradition with external influences. The polarization within the MPB field created the possibility of emergence of new positions and external articulation. The change within these logics took place in tandem with the drawing of new boundaries and new career trajectories around and within these fields. In contrast, these conflicts revealed shared elements that became eventually institutionalized and shared by opposing groups.